Gambaran Pengetahuan Masyarakat tentang Vaksin Covid-19 di Dusun Manis Desa Padarek Kabupaten Kuningan - Marlinda Sari, Liska; Puspa Dynesha, Bella (LP4M STIKes Karsa Husada Garut, 2023)
Introduction: Covid-19 vaccine is one of the government's breakthrough to fight and handle Covid-19 in the world, especially in Indonesia. In Kuningan Regency, especially in Padarek Village, the vaccination rate has not reached 100%. As of July 25, 2022, the first dose has reached 80%, the second dose has reached 73.9%, and the third dose has reached 12.6%. Methods: The purpose of this study is to describe the knowledge of the community about the Covid-19 vaccine in Padarek Village, Kuningan Regency in 2022. Results: Based on the results of the study, it was concluded that the majority of respondents were in the vulnerable age group (46-55 years). Of the 100 respondents, 54% of the people in Padarek Village have good knowledge about Covid-19 vaccines, 39% have sufficient knowledge, and 7% have less knowledge. This is due to the lack of information about Covid-19 vaccines. 68% of respondents are willing to get vaccinated against Covid-19, while 32% are not willing to get vaccinated for several reasons. Conclusion: The results of this study reported that more than half of the people in Padarek Village have good knowledge, while less than half have sufficient knowledge, and a small portion have less knowledge about Covid-19 vaccines.